Optimalisasi Layanan M-Paspor Dari Sudut Pandang Responsiveness dan Reliability di Kantor Imigrasi Denpasar - Putu Denny Artina Mahendra; Komang Adi Sastra Wijaya; I Ketut Winaya (Program Studi Administrasi Negara Universitas Serang Raya, 2024)
Submitting passport application already uses the M-Passport application carrying out services. The Director General of Immigration of Indonesia created the M-Passport application innovation to facilitate passport services. This study aims to determine how the optimization of M-Passport services from the point of view of responsiveness and reliability at Denpasar Immigration Office. Qualitative methods are used to explore information on phenomenon supported by descriptive approach so that informants are comfortable when conducting interviews. Data sources come from interviews and documents related to the research. Data were collected through documentation, interviews, and observations at research location. Then data was analyzed by data reduction, data presentation and conclusion drawing. The result of the discussion of this research is that the service of submitting passport applications at Denpasar Immigration Office is quite optimal, but there needs to be improvement in several service components such as need to improve the process of interview queuing systems, fingerprint scanning, and photo taking, creating synergies between immigration officers so that information conveyed is appropriate between employees, and creating synergies with the Director General of Immigration of Indonesia regarding the development of the M-Passport application.